Cancer Warning Symptoms Awareness and Associated Factors Among Individuals Living in Assella Town, Ethiopia - Admasu Belay Gizaw; Helina Tadesse Gutema; Gugsa Nemera Germossa (SAGE Publishing, 2021)
Introduction Community awareness about cancer warning symptoms and risk factors in the general population is essential and can be considered as a basis for cancer control programs. Since Patients are rarely aware of the early warning symptoms and cancer risk factors, the burden of disease is increasing everywhere in the world. Evidences has been shown that cancer is highly prevalent in Ethiopia in which the diagnosis is made at later stages of the disease. Objective To assess Cancer Warning Symptoms awareness and associated factors among individuals living in Assella Town, Ethiopia. Methods A community-based cross-sectional study was employed in Assella town from May 1 st to June 1 st , 2020 among 410 adult residents 18 years old and above. A systematic random sampling technique was employed to select the households from which the study subjects randomly identified. Data were collected through face-to-face interview by using pre-tested structured questionnaire and entered into Epi data version 3.1 then exported to SPSS version 25.0 for analysis. Logistic regression analyses were used to identify factors associated with outcome variables. Odds ratio and 95% CI at P-values <0.05 was used to determine the presence of association. Results The findings of this study revealed that the overall level of awareness of cancer warning symptoms is 214 (52.2% (AOR = 95% CI 47.1, 56.8)). Educational level (AOR = 3.44, 95%CI, 1.50-7.88 (p = 0.003)), awareness of cancer risk factors (AOR = 2.56, 95% CI, 1.67, 3.93, (p < 0.001)) and economic status (AOR = 3.13 (95% CI 1.84, 5.33, p < 0.001)) were identified as factors significantly associated with awareness of cancer warning symptoms among adult populations. Conclusion Almost one-out-of-two adults residing in Assella town has awareness about cancer warning symptoms. Educational level, awareness of cancer risk factors, and economic status among Assella town residents were identified as factors associated with good level of awareness about cancer warning symptoms.